2013
DOI: 10.1128/jvi.00371-13
|View full text |Cite
|
Sign up to set email alerts
|

Systems To Establish Bunyavirus Genome Replication in the Absence of Transcription

Abstract: The L polymerase of bunyaviruses replicates and transcribes the viral genome. While replication products are faithful copies of the uncapped genomic RNA, transcription products contain capped 5= extensions which had been cleaved from host cell mRNAs. For La Crosse virus (LACV; genus Orthobunyavirus), the nuclease responsible for host cell mRNA cleavage is located at the N terminus of the L protein, with an active site of five conserved amino acids (H34, D52, D79, D92, and K94) surrounding two Mn 2؉ ions (J. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 50 publications
2
29
1
Order By: Relevance
“…The endonuclease domain of LACV (genus Orthobunyavirus) is situated at the N terminus of the L protein. Sequence alignments indicated a similar N-terminal endonuclease domain for three other Bunyaviridae genera, Phlebovirus, Hantavirus, and Tospovirus (32), and for phleboviruses, this was confirmed by functional data (21,22). For the genus Nairovirus (to which CCHFV belongs), however, the N terminus of the L protein harbors the so-called OTU domain, which has immune escape function (33).…”
Section: Generation Of Cchf Virus-like Particles Expressing a Reportementioning
confidence: 84%
See 4 more Smart Citations
“…The endonuclease domain of LACV (genus Orthobunyavirus) is situated at the N terminus of the L protein. Sequence alignments indicated a similar N-terminal endonuclease domain for three other Bunyaviridae genera, Phlebovirus, Hantavirus, and Tospovirus (32), and for phleboviruses, this was confirmed by functional data (21,22). For the genus Nairovirus (to which CCHFV belongs), however, the N terminus of the L protein harbors the so-called OTU domain, which has immune escape function (33).…”
Section: Generation Of Cchf Virus-like Particles Expressing a Reportementioning
confidence: 84%
“…1B and D). Experiments employing a neutralizing antibody showed that the GP-mediated boost (which was also observed for LACV and RVFV systems, though in a less extreme manner [18,22]) is due to reinfection of transfected cells by the generated VLPs (data not shown). Differently from the previously published minireplicon system (14), we obtained very little background activity by the minigenome plasmid if transfected without L polymerase (data not shown).…”
Section: Generation Of Cchf Virus-like Particles Expressing a Reportementioning
confidence: 99%
See 3 more Smart Citations